Diverse energy transition patterns in Central and Southern Europe: a comparative study of institutional landscapes in the Czech Republic, Hungary, Italy, and Spain - Frolova, Marina; Frantál, Bohumil; Ferrario, Viviana; Centeri, Csaba; Herrero-Luque, Daniel; Grónás, Viktor; Stanislav, Martinát; Puttilli, Matteo; Almeida, Lucas; D'Angelo, Fabrizio (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
Growing awareness of anthropogenic climate change, deep cuts in CO2 emissions, and the exhaustion of easy-to-extract fossil fuels have led to a growing interest in developing renewable energy sources as a part of the (desired) transition to a low-carbon society. The target of the European Union for 2020 is to cover 20% of final energy consumption by renewable energy sources, and for 2030 it should reach at least 32%. While there are ambitious goals to boost the energy transition, it is becoming increasingly evident that the processes run differently in different countries, some of which still prefer path-dependent options and resist major changes. This comparative study applies a historical institutionalist approach to examine the institutional factors influencing the development of renewable energies in the Czech Republic, Hungary, Italy and Spain, countries with different geographies, political and socio-cultural traditions, belonging respectively to Central and Southern Europe, whose comparison has so far been largely neglected in the literature. The general objective of this paper is to investigate and exemplify how diverse energy traditions, institutional frameworks, policies, and practices shape the processes and outcomes of the renewable energy transition.
Keywords: renewable energy; institutional landscapes; drivers of transition; policy; comparative analysis